Is technology enhanced learning an interdisciplinary activity? - Scanlon, Eileen; Taylor, Josie (Proceedings of the International Conference on Networked Learning, 2016)
This paper describes an approach to working in educational technology informed by the recognition of the subject as a major current site for interdisciplinary activity. Currently the most popular term for educational technology embraced in the UK and in the EU is Technology Enhanced Learning (TEL). We draw on the literature on interdisciplinary and multi-disciplinary working, contemporary rationales for interdisciplinarity as an imperative for meeting the challenges of knotty real world problems, and the experience of working in interdisciplinary teams in TEL. The purpose is to establish the particular features of this collaborative research effort. This perspective from literature and contemporary rhetoric around practice is supplemented with reference to several interview studies of TEL project teams. These studies outlined the advantages in terms of growth, multiple perspectives and design methodologies but also the challenges in terms of sustainability, career progression and publication, the benefits of technologies for communication within teams and distinctive working practices (Jordan et al. 2012, Conole et al., 2010, Scanlon et al., 2013).